Artificial Intelligence, Regulatory Frameworks, And Human Rights: Rethinking Conflict Resolution in The Digital Era in West Pokot County, Kenya (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Artificial Intelligence (AI) is increasingly recognized as a transformative tool in governance, peace building, and social development, particularly in conflict-prone regions such as West Pokot County, Kenya, where intercommunal clashes, cattle rustling, and cross-border disputes persist. This study investigates the integration of AI into conflict resolution while ensuring the protection of human rights under Kenya’s regulatory frameworks. The objectives were to examine the opportunities and risks associated with AI in peace building, evaluate the adequacy of existing legal and ethical safeguards, and propose models that balance technological innovation with community-driven conflict resolution strategies. A mixed-methods design was employed, engaging 60 purposively selected respondents, including government officials, community leaders, human rights activists, members of peace committees, and youth representatives. Data were collected through semi-structured interviews, focus group discussions, and document reviews of policy frameworks and human rights reports.To strengthen the robustness of findings, both quantitative statistical analyses (descriptive statistics, cross-tabulations, Chi-square tests, and factor analysis) and qualitative thematic coding were employed. Results indicate that AI applications particularly predictive analytics, mobile-based early warning systems, digital mediation platforms, and resource-mapping tools hold significant potential to enhance conflict anticipation, coordination, and resolution. However, gaps in regulatory enforcement, algorithmic bias, digital exclusion of women and elderly populations, and infrastructural limitations constrain effective implementation. The study highlights a critical knowledge gap between global AI innovations and localized conflict management practices in marginalized regions.Sustainable peace in West Pokot requires a hybrid governance model that integrates AI-driven tools with culturally grounded conflict resolution mechanisms, reinforced by robust human rights protections and inclusive leadership. Recommendations include strengthening Kenya’s AI-specific legal and ethical frameworks, investing in community-focused digital literacy, piloting scalable AI interventions, and establishing safeguards to prevent misuse in fragile contexts. By aligning technological innovation with community needs and ethical oversight, AI can become a complementary mechanism for building sustainable peace and resilience in conflict-affected areas.